Strategies To Increase Public Acceptance Of Carbon Tax Policy In Indonesia Using Participatory And Educative Approaches - Frania Audrey Marisya; Meily Putri Shofwatul Ashfiya ‘Umami; Ariana Setyaningrum (International Journal of Economics Accounting and Management, 2024)
Climate change is a major threat to the global ecosystem and economy. One of the policies promoted to reduce greenhouse gas (GHG) emissions that are the main drivers of climate change is the carbon tax policy. However, the implementation of carbon tax in Indonesia is not simple and faces many challenges, including low public acceptance of the policy. The method used in compiling this article is a literature study approach to understand the concept, theory, and findings of previous research related to the implementation of carbon tax and the factors that influence the level of public acceptance. The results of the study indicate that if the Carbon Tax is to be accepted by the public, the Government must provide an opportunity for its citizens to provide opinions, build trust, and draft policies fairly and transparently. This needs to be done so that the Carbon Tax is not merely viewed as a fiscal instrument, but also as a form of shared commitment to a more sustainable future